Asymmetric trophallaxis between workers of the stingless bee Melipona quadrifasciata (Apidae, Meliponini) - Contrera, Felipe Andrés León; Imperatriz-Fonseca, Vera Lúcia; Koedam, Dirk [UNESP] (My University, 2011)
In several species of social insects, there is a positive relationship between the food exchange that occurs during trophallaxis and the ovarian development of workers, indicating that food transfers are important for the establishment of reproductive hierarchies between the colony members. In this chapter, we tested if such correlations also occur between workers of the stingless bee Melipona quadrifasciata anthidioides. Due to the difficulty to follow the totality of worker behavior inside the nest, we housed six newly-emerged workers in confined conditions, away from the mother colony and older workers, with pollen and honey ad libitum and under stable conditions of temperature and illumination. We measured their trophallactic behavior until the moment the first worker died; after that all workers from the group were dissected for the measure of their ovarian development. We found significant differences in the individual trophallactic behavior exhibited by workers, since some workers were mainly food donors whereas others were mainly receivers, and all contacts were initiated by the soliciting bee. Moreover, only 15% of the trophallactic contacts were longer than one second, and thus, possibly resulted in an effective food exchange. However, there was no correlation between the ovarian development and the trophallactic behavior of workers, which might be caused by the experimental conditions the workers were kept, and the small age they died, which was five days after the start of the experiment. However, considering that Melipona workers from different species highly vary in their ovarian development and egg-laying capacities, and that individual workers exhibit significant differences in their trophallactic behavior, it is reasonable to presume that under natural conditions trophallaxis might have a relevant role in their ovarian development, but this possibility yet remains to be tested in regular colonies. © 2011 Nova Science Publishers, Inc. All rights reserved.
Keywords: Food share; Melipona; Ovarian development